Hypovirulence of Sclerotium rolfsii Caused by Associated RNA Mycovirus - Zhong, Jie; Chen, Dan; Zhu, Hong J.; Gao, Bi D.; Zhou, Qian (Frontiers in Microbiology, 2016)
Mycoviruses associated with hypovirulence are potential biological control agents and could be useful to study the pathogenesis of fungal host pathogens. Sclerotium rolfsii, a pathogenic fungus, causes southern blight in a wide variety of crops. In this study, we isolated a series of dsRNAs from a debilitated S. rolfsii strain, BLH-1, which had pronounced phenotypic aberrations including reduced pathogenicity, mycelial growth and deficient sclerotia production. Virus-curing and horizontal transmission experiments that eliminated or transmitted, respectively, all dsRNA elements showed that the dsRNAs were involved in the hypovirulent traits of BLH-1. Ultrastructure examination also showed hyphae fracture and cytoplasm or organelle degeneration in BLH-1 hyphal cells compared to the virus-free strain. Three assembled cDNA contigs generated from the cDNA library cloned from the purified dsRNA indicated that strain BLH-1 was infected by at least three novel mycoviruses. One has similarity to the hypovirulence-associated Sclerotinia sclerotiorum hypovirus 2 (SsHV2) in the family Hypoviridae, and the other two are related to two different unclassified dsRNA mycovirus families. To our knowledge, this is the first report of S. rolfsii hypovirulence that was correlated with its associated dsRNA.